Pengauditan Sistem Informasi Pendaftaran Sidang dan Wisuda Menggunakan Framework COBIT 5 pada Domain EDM04 dan APO07 - Syahrani Arrahma; Aldi Wicaksono; Farhan Rizky Wahyudi; Muhammad Rezeki Fasya; Supiyandi (LKP KARYA PRIMA KURSUS, 2024)
This study aims to assess the effectiveness and efficiency of the Session Registration and Graduation Information System (SI-RASIDA) at the State Islamic University of North Sumatra using the COBIT 5 framework in the EDM04 and APO07 domains. The COBIT 5 framework in auditing information systems provides a solid foundation to ensure the system meets completeness, provides added value for users, and complies with applicable IT management standards. Qualitative methods are used by applying this framework to measure system performance. The results show that in resource optimization, the current condition has a value of 3.20 with a capability level of 3, while the expected condition has a value of 4.58 with a capability level of 5. In human resource management, the current condition shows a value of 3.47 with a capability level of 3, while the expected condition reaches a value of 4.76 with a capability level of 5. This data indicates a significant gap between the current and expected conditions, with a capability difference of 2 levels. Recommendations for improvement include improving communication, implementing technology, establishing clear roles and responsibilities, developing performance metrics, integrating resource strategies with budgets, documenting HR policies, using HR management software, and continuous training programs. The implementation of these improvement recommendations is expected to optimize resource management and HR management, achieve a higher level of capability, and support the achievement of the strategic objectives of the State Islamic University of North Sumatra.